Exploring the efficacy of fluorouracil and platinum based chemotherapy in advanced hepatocellular carcinoma to bridge the treatment gap in resource limited settings - Se Jun Park; Kabsoo Shin; In-Ho Kim; MyungAh Lee; Tae Ho Hong; Hyunho Kim (Scientific Reports)
Abstract Advanced hepatocellular carcinoma (HCC) poses treatment challenges, especially where access to multi-kinase inhibitors and ICIs is limited by high costs and lack of insurance. This study evaluates the effectiveness of 5-fluorouracil (5-FU) plus platinum-based chemotherapy as an alternative systemic treatment for advanced HCC. A retrospective analysis of advanced HCC patients treated with 5-FU plus platinum-based chemotherapy was conducted. The Kaplan-Meier method determined median progression-free survival (PFS) and overall survival (OS). From April 2009 to October 2023, 48 patients with advanced HCC were included in the study. Nearly all patients (97.9%) had extrahepatic metastasis and stable liver function, with three-quarters previously treated with sorafenib. At a median follow-up of 7.8 months, the median PFS was 4.2 months (95% CI, 1.3–7.1), and the median OS was 8.2 months (95% CI, 2.5–13.9). A high pretreatment neutrophil-to-lymphocyte ratio (≥ 3.0) adversely affected both PFS (HR = 1.79; 95% CI, 0.99–3.25; p = 0.034) and OS (HR = 2.02; 95% CI, 1.10–3.69; p = 0.011). Hematologic toxicities related to the treatment were substantial, with 62.5% of patients experiencing grade 3 or 4 events, primarily neutropenia, which affected 60.4% of them. Our findings suggest that 5-FU combined with platinum-based chemotherapy is a viable, cost-effective alternative for advanced HCC treatment in resource-limited settings, particularly compared to ICIs and multi-kinase inhibitors, with significant implications for developing countries.